2014
DOI: 10.5395/rde.2014.39.4.282
|View full text |Cite
|
Sign up to set email alerts
|

Push-out bond strength of a self-adhesive resin cement used as endodontic sealer

Abstract: ObjectivesThe aim of the present study was to investigate the bond strength of RelyX Unicem (3M) to root canal dentin when used as an endodontic sealer.Materials and MethodsSamples of 24 single-rooted teeth were prepared with Gates Glidden drills and K3 files. After that, the roots were randomly assigned to three experimental groups (n = 8) according to the filling material, (1) AH Plus (Dentsply De Trey GmbH)/Gutta-Percha cone; (2) Epiphany SE (Pentron)/Resilon cone; (3) RelyX Unicem/Gutta-Percha cone. All ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…The BS values obtained for specimens in the control group ranged from 6.35 MPa to 7.13 MPa, in agreement with previous studies that reported values between 4.56 MPa[ 23 ] and 9.3 MPa. [ 24 ] The presence of an intact dentin, clean and with unaltered structure, allows adequate entanglement of materials, which is fundamental for formation of the hybrid layer, characterized as the space corresponding to resin infiltration within the collagen matrix.…”
Section: Discussionsupporting
confidence: 91%
“…The BS values obtained for specimens in the control group ranged from 6.35 MPa to 7.13 MPa, in agreement with previous studies that reported values between 4.56 MPa[ 23 ] and 9.3 MPa. [ 24 ] The presence of an intact dentin, clean and with unaltered structure, allows adequate entanglement of materials, which is fundamental for formation of the hybrid layer, characterized as the space corresponding to resin infiltration within the collagen matrix.…”
Section: Discussionsupporting
confidence: 91%
“…The difference in bond strengths between the two sealer systems tested was not unexpected. Previous literature has identified higher bond strengths of gutta‐percha and AH Plus compared to Resilon and RealSeal SE to dentin . The AH Plus sealer has a strong wetting effect, allowing it to penetrate into irregularities in the instrumented dentin and the open tubules in the root canal .…”
Section: Discussionmentioning
confidence: 99%
“…A research conducted by Yahya et al also showed that the highest bond strength was attained by RelyX TM Unicem as compared to Elite 100 ® zinc phosphate cement, Calibra and RelyX ARC resin cement ( 27 ). Apart from that, a good bond strength was obtained for RelyX TM Unicem ( 28 ). There are many possible explanations behind the superior bond strength of RelyX TM Unicem as compared to several other luting cements.…”
Section: Discussionmentioning
confidence: 98%